2005
DOI: 10.1080/02844310410021730
|View full text |Cite
|
Sign up to set email alerts
|

Three-year evaluation of late breast reconstruction with a free transverse rectus abdominis musculocutaneous flap in a county hospital in Sweden: A retrospective study

Abstract: We present our three-year experience of late breast reconstruction with conventional free TRAM flaps in 16 consecutive patients in a Swedish county hospital. The breast reconstruction was done unilaterally in 14 and bilaterally in two, giving a total of 18 free TRAM flaps in 16 patients. Six patients developed anastomotic or systemic thromboembolic events during or after the operation' three developed during the operation, and one required reoperation for postoperative thrombosis. No flaps were lost. Three pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…7,16,[25][26][27] There have been several reports of the use of free tissue transfer in the community hospital setting, generally involving a small number of surgeons with the assistance of residents. 6,[28][29][30] Maffi reported an 85% success rate with 53 free flaps in 49 patients by a team consisting of one attending with a plastic surgery resident and a general surgery resident in a county hospital. 6 Olsson reported 18 free TRAM flaps in 16 patients with no flap losses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,16,[25][26][27] There have been several reports of the use of free tissue transfer in the community hospital setting, generally involving a small number of surgeons with the assistance of residents. 6,[28][29][30] Maffi reported an 85% success rate with 53 free flaps in 49 patients by a team consisting of one attending with a plastic surgery resident and a general surgery resident in a county hospital. 6 Olsson reported 18 free TRAM flaps in 16 patients with no flap losses.…”
Section: Discussionmentioning
confidence: 99%
“…6 Olsson reported 18 free TRAM flaps in 16 patients with no flap losses. 29 The procedures were apparently performed by a team of surgeons. Elliott described a series of 111 free TRAM flaps in 100 patients in a private practice setting without flap loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence has been reported to vary from 0.7 to 18.8 percent. 10,11 In a prospective assessment of the incidence of pulmonary thromboembolism in patients undergoing immediate TRAM flap breast reconstruction without medical prophylaxis, we observed an overall incidence of 1.3 percent, and the incidence was raised to 3.8 percent in obese patients. 12 We also found that the incidence of symptomatic or asymptomatic pulmonary thromboembolism in immediate TRAM flap breast reconstruction patients was 20.4 percent.…”
mentioning
confidence: 95%
“…Segundo dados da literatura, a incidência de TVP no lifting facial é 0,35% 1 , na lipoaspiração é 0,6% 2 , em abdominoplastias é cerca de 1,3% 3,4 (abdominoplastia circunferencial e a associada a cirurgia intra-abdominal apresentam incidência de TVP, respectivamente, de 3,4 e 2,17%) 5 e no retalho transverso do músculo reto abdominal (TRAM) monopediculado é 1,3% 6 . Em relação à EP, a incidência também não é definida: no lifting facial é estimada em 0,14% 1 , em abdominoplastias, 0,8% 3 (se associado a outras cirurgias, varia de 1,1% 7 a 6,6% 8 ), na lipoaspiração, 1,1% 2 , e no retalho TRAM varia de 0,7 a 18,8% 9,10 .…”
Section: Introductionunclassified